PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PADA SISWA KELAS XI SMA NEGERI 73 JAKARTA - Daniel Dongan Parulian Siagian; Santri Chintia Purba; Kerdid Simbolon (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
Education plays an important role in the development of science and technology by creating skilled human resources. In learning activities, motivation and of course the learning outcomes themselves cannot be separated. Experts say that good learning outcomes are influenced by high motivation. The purpose of this research is to find out whether there is influence between students' learning motivation and student learning outcomes. This research was conducted at SMA Negeri 73 Jakarta Class XI in the even semester of the academic year. This study uses a survey method to find the relationship between variables with a simple linear regression technique. Sampling used was purposive sampling, amounting to 150 students. Instruments in the form of a questionnaire / questionnaire learning motivation and daily test scores of all students of class XI. Based on the results of the hypothesis test, it is known that there is an influence between the learning motivation variable on the learning outcomes of class XI students in the compulsory mathematics subject at SMA Negeri 73 Jakarta. The results showed that the simple regression model can be used to predict learning motivation variables on learning outcomes, or there is an effect of learning motivation variables (X) on learning outcomes (Y), with a significance level of 0.000 < 0.05.